Teaching Legal History – History of Legal Teaching: Introductory Remarks - Korporowicz, Łukasz Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The article works as a set of introductory remarks that precede the collection of articles published under the title Teaching Legal History – History of Legal Teaching. In this article, the aims of the volume and its content are discussed.